Public Relations to Foster Organization's Values and Identity: The Case of Muhammadiyah - Sumarlan, Iman; T.I.Ukka, Ibrahim (Universitas Muhammadiyah Yogyakarta, 2024)
This study examines the strategic role of public relations in religious organizations, focusing on how Muhammadiyah employs communication to foster its organizational values and reinforce its identity. By adopting Pacanowsky’s cultural approach to organizational theory, the research delves into how symbols, narratives, and rituals inherent in Muhammadiyah’s culture are effectively integrated into its public relations strategy. A qualitative methodology was employed, including in-depth interviews and document analysis, to explore how these cultural elements are embedded in communication practices. The findings reveal that Muhammadiyah carefully aligns its public relations efforts with its organizational culture, enabling an authentic representation of its values to internal and external stakeholders. The study underscores the significance of maintaining consistency between an organization's identity, values, and communication strategies, particularly for religious institutions. It concludes that strategically incorporating cultural elements into communication not only preserves organizational integrity but also enhances the institution's relevance and influence in its broader societal context.